2018
DOI: 10.1007/s00520-018-4179-0
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors’ experiences of a community-based cancer-specific exercise programme: results of an exploratory survey

Abstract: Community-grown exercise initiatives bring cancer survivors together creating their own supportive environment. Combining this with instructors familiar with the population and providing an open-ended service may prove particularly motivating and beneficial. Further work is required to provide evidence for this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…Others (21%) primarily focused on describing program development and implementation 24,32,33,38,40,47,50,52,57,63,72,80 . Thirteen publications (22%) reported participants' experiences in community-based exercise programs using a qualitative 27,30,31,49,51,55,62,64,69,81 or cross-sectional survey design 29,34,75 ; two (3%) were study protocol papers 39,79 and two (3%) described hybrid implementation-effectiveness trials 26,28 .…”
Section: Description Of Included Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Others (21%) primarily focused on describing program development and implementation 24,32,33,38,40,47,50,52,57,63,72,80 . Thirteen publications (22%) reported participants' experiences in community-based exercise programs using a qualitative 27,30,31,49,51,55,62,64,69,81 or cross-sectional survey design 29,34,75 ; two (3%) were study protocol papers 39,79 and two (3%) described hybrid implementation-effectiveness trials 26,28 .…”
Section: Description Of Included Publicationsmentioning
confidence: 99%
“…Programs ranged from four weeks 38 to one year 26 in duration. Five programs did not describe specific program lengths 34,40,53,54,64,71 . Most programs included a combination of aerobic and resistance exercise (62%) 24, 25, 27, 31, 34-36, 39, 40, 43-48, 50, 52-63, 67-71, 73, 74, 76, 78 , while others described only resistance training 26,41,65,77 , or aerobic exercise 30,37,72 .…”
Section: Intervention Characteristics (Table 1)mentioning
confidence: 99%
“…The most frequently reported barriers among all cancer survivors included competing time commitments between work and personal recreation and treatment-related limitations such as physical discomfort or fatigue. [10][11][12][13] Cost of gym memberships or exercise class participation was a reported barrier for survivors from lower S.E.S. backgrounds but was not concretely associated with race alone.…”
Section: Physical Activitymentioning
confidence: 97%
“…Group based exercise can create a sense of belonging and sociability rather than just exercising [48], [49]. Previous research found that having activities tailored to their ability and group support were two important benefits of a community-based exercise programme [50].…”
Section: Critical Factors For An Exercise Pathway For Cancer Patientsmentioning
confidence: 99%